Occupy time: technoculture, immediacy, and resistance after occupy wall street - Adams, Jason M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
While secondary texts on Paul Virilio typically see no way out of the tempo- and techno-dystopia he articulates, Occupy Time engages the events of Occupy Wall Street to fix attention on what such readings circumvent: Virilio's elusive theory of resistance.
Keywords: Political theory; Europe -- Politics and government; Terrorism; Social sciences -- Philosophy